Differential Response of Potato Toward Inoculation with Taxonomically Diverse Plant Growth Promoting Rhizobacteria - Naqqash, Tahir; Hameed, Sohail; Imran, Asma; Hanif, Muhammad Kashif; Majeed, Afshan; van Elsas, Jan Dirk (Frontiers in Plant Science, 2016)
Rhizosphere engineering with beneficial plant growth promoting bacteria offers great promise for sustainable crop yield. Potato is an important food commodity that needs large inputs of nitrogen and phosphorus fertilizers. To overcome high fertilizer demand (especially nitrogen), five bacteria, i.e. Azospirillum sp.TN10, Agrobacterium sp.TN14, Pseudomonas sp.TN36, Enterobactersp. TN38 and Rhizobium sp. TN42 were isolated from the potato rhizosphere on nitrogen-free malate medium and identified based on their 16S rRNA gene sequences. Three strains, i.e. TN10, TN38 and TN42, showed nitrogen fixation (92.67-134.54 nmol h-1mg-1protein), while all showed the production of indole acetic acid in the presence and/or absence of L-tryptophan. Azospirillum sp. TN10 produced the highest amount of IAA, as measured by spectrophotometry (312.14 µg mL-1) and HPLC (18.3 µg mL-1). Inoculation with these bacteria under axenic conditions resulted in differential growth responses of potato. Azospirillum sp. TN10 incited the highest increase in potato fresh and dry weight over control plants, along with increased N contents of shoot and roots. All strains were able to colonize and maintain their population densities in the potato rhizosphere for upto 60 days, with Azospirillum sp. and Rhizobium sp. showing the highest survival. Plant root colonization potential was analyzed by transmission electron microscopy of root sections inoculated with Azospirillum sp. TN10. Of the five test strains, Azospirillum sp. TN10 has the greatest potential to increase the growth and nitrogen uptake of potato. Hence, it is suggested as a good candidate for the production of potato biofertilizer for integrated nutrient management with potato.